2017
DOI: 10.1371/journal.pone.0173918
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a regulates glucose induced upregulation of inflammatory cytokines extracellular matrix proteins in the retina and kidney in diabetes

Abstract: Hyperglycemic damage to the endothelial cells (ECs) leads to increased synthesis of inflammatory cytokines. We have previously shown miR-146a downregulation in ECs and in the tissues of diabetic mice. Here we investigated the role of miR-146a, in the production of specific inflammatory cytokines and extracellular matrix (ECM) proteins in retina and kidneys in diabetes. We generated an endothelial specific miR-146a overexpressing transgenic mice (TG). We investigated these mice and wild type (WT) controls with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 63 publications
0
38
0
Order By: Relevance
“…Measurement of urinary albumin and creatinine was performed by ELISA (Albuwell M; Exocell, Philadelphia, PA). All procedures were performed using the manufacturer's protocol, and the data were used to calculate urinary albumin/creatinine ratio (16).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Measurement of urinary albumin and creatinine was performed by ELISA (Albuwell M; Exocell, Philadelphia, PA). All procedures were performed using the manufacturer's protocol, and the data were used to calculate urinary albumin/creatinine ratio (16).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…MiR-146a downregulation may worsen inflammation within the ALI model. Chen et al (15) indicated that miR-146a may regulate glucose-induced inflammation of the retina and kidney in diabetes or animal/in vitro models. Endogenous nitric oxide (NO) is a free radical with high activity, and serves as a signaling molecule and a toxic molecule with diverse biological functions (4).…”
Section: Discussionmentioning
confidence: 99%
“…Plates were measured at 450 and 570 nm (to correct for plate defects) using a plate reader. For detection of albumin and creatinine in mouse urine, Albuwell™ and Creatinine Companion kits were used from Exocell (Philadelphia, PA, USA) …”
Section: Methodsmentioning
confidence: 99%